2010
DOI: 10.1007/s11104-010-0650-5
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus saturation and pH differentially regulate the efficiency of organic acid anion-mediated P solubilization mechanisms in soil

Abstract: Exudation of organic acid anions by plants as well as root-induced changes in rhizosphere pH can potentially improve phosphate (P i ) availability in the rhizosphere and are frequently found to occur simultaneously. In non-calcareous soils, a major proportion of P i is strongly sorbed to metal oxi (hydr)oxides of mainly iron (Fe) and aluminium (Al) and organic anions are known to compete with P i for the same sorption sites (ligand exchange) or solubilize P i via ligand-promoted mineral dissolution. Rootinduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
132
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(144 citation statements)
references
References 36 publications
(43 reference statements)
9
132
0
3
Order By: Relevance
“…Phosphate in the soil solution can interact as a ligand with soluble cations such as Ca, Mg, Fe, and Al, among others, changing their availability and mobility (Girotto et al, 2010;Oburger et al, 2011). Continued applications of PS, a multielement fertilizer, are expected to induce changes in the chemical composition and distribution of P species in the soil solution, together with crop cultivation, which can alter the concentration of elements in the soil solution by absorption and accumulation in plant tissues, by exudation of organic compounds and by changes in pH through the release of OH -or H + (Gahoonia et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphate in the soil solution can interact as a ligand with soluble cations such as Ca, Mg, Fe, and Al, among others, changing their availability and mobility (Girotto et al, 2010;Oburger et al, 2011). Continued applications of PS, a multielement fertilizer, are expected to induce changes in the chemical composition and distribution of P species in the soil solution, together with crop cultivation, which can alter the concentration of elements in the soil solution by absorption and accumulation in plant tissues, by exudation of organic compounds and by changes in pH through the release of OH -or H + (Gahoonia et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Although it is well documented that citrate (and protons) is able to mobilize P in soil (Hoffland 1992;Geelhoed et al 1999;Kirk et al 1999;Hinsinger 2001;Oburger et al 2011), there are contrasting reports on root exudation of citrate or other low molecular weight organic acids under Zn deficiency and/ or their potential to mobilize Zn in soil. On the one hand Rose et al (2011) proposed that enhanced exudation of malate, but not citrate, is a response of Znefficient rice genotypes to Zn deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…For both soils, P desorption in response to citrate application was higher than P desorption with water, in view of the competition of citrate with P for similar soil sorption sites, as already noted by other authors (Geelhoed et al, 1999;Johnson & Loeppert, 2006;Moradi et al, 2012). Oburger et al (2011a) observed a similar response in P desorption with citrate addition, causing a mean desorption of 13.0 % of the P applied to the soil and only 3.0 % of P was desorbed with water after an application of 24 mg kg -1 P. Phosphorus desorption by citrate can occur under natural conditions by root exudation or organic matter decomposition (Johnson & Loeppert, 2006;Pavinato & Rosolem, 2008). More than 99 % of the organic acid exudates remain within a distance of 1 mm from the root surface, increasing the chances of P desorption in this region (Jones et al 1996).…”
Section: Incubation Time and Soil P Desorptionmentioning
confidence: 99%
“…Organic acids can be retained in the soil with high energy and block P sorption sites (Haynes, 1984). The carboxylic groups, characteristic of these organic acids, can dissociate and release protons in a wide pH range and promote the dissolution of soil minerals (Andrade et al, 2003;Oburger et al, 2011a). A great effectiveness of citrate was noted in the competition for P sorption sites; this greater competitiveness is due to the higher number of carboxylic groups (tricarboxylic).…”
Section: Introductionmentioning
confidence: 99%